Low Glucose Mediated Fluconazole Tolerance in Cryptococcus neoformans - Somanon Bhattacharya; Natalia Kronbauer Oliveira; Anne G. Savitt; Vanessa K. A. Silva; Rachel B. Krausert; Berhane Ghebrehiwet; Bettina C. Fries (Journal of Fungi, 2021)
Chronic meningoencephalitis is caused by Cryptococcus neoformans and is treated in many parts of the world with fluconazole (FLC) monotherapy, which is associated with treatment failure and poor outcome. In the host, C. neoformans propagates predominantly under low glucose growth conditions. We investigated whether low glucose, mimicked by growing in synthetic media (SM) with 0.05% glucose (SMlowglu), affects FLC-resistance. A > 4-fold increase in FLC tolerance was observed in seven C. neoformans strains when minimum inhibitory concentration (MIC) was determined in SMlowglu compared to MIC in SM with normal (2%) glucose (SMnlglu). In SMlowglu, C. neoformans cells exhibited upregulation of efflux pump genes AFR1 (8.7-fold) and AFR2 (2.5-fold), as well as decreased accumulation (2.6-fold) of Nile Red, an efflux pump substrate. Elevated intracellular ATP levels (3.2-fold and 3.4-fold), as well as decreased mitochondrial reactive oxygen species levels (12.8-fold and 17-fold), were found in the presence and absence of FLC, indicating that low glucose altered mitochondrial function. Fluorescence microscopy revealed that mitochondria of C. neoformans grown in SMlowglu were fragmented, whereas normal glucose promoted a reticular network of mitochondria. Although mitochondrial membrane potential (MMP) was not markedly affected in SMlowglu, it significantly decreased in the presence of FLC (12.5-fold) in SMnlglu, but remained stable in SMlowglu-growing C. neoformans cells. Our data demonstrate that increased FLC tolerance in low glucose-growing C. neoformans is the result of increased efflux pump activities and altered mitochondrial function, which is more preserved in SMlowglu. This mechanism of resistance is different from FLC heteroresistance, which is associated with aneuploidy of chromosome 1 (Chr1).